Inselbergs: potential conservation areas for plant diversity in the face of anthropization - Tindano, Elycée; Lankoandé, Benjamin; Porembski, Stefan; Thiombiano, Adjima (Journal of Phytology, 2023)
Faced with the loss of biodiversity, particularly plant diversity, due to anthropogenic pressure, particular ecosystems such as inselbergs can constitute refuge areas. The objective of this study is to determine the conservation potential of plant biodiversity on inselbergs in Burkina Faso. A comparative study was carried out between inselberg’s vegetation and the surrounding plains vegetation. In each of these vegetation types, stratified and random sampling was adopted and data were collected in plots of 900 m² for the woody stratum and 100 m² for the herbaceous stratum. The specific diversity was evaluated through the effective numbers of Hill of order Q = 0; 1; 2. The Hill index does not vary between inselbergs and plains and thus reflects a strong similarity in floristic diversity between the two ecosystems. Sorensen’s similarity coefficient also shows a similarity in terms of floristic composition between inselbergs and surrounding plains. In inselbergs, relict species that have disappeared from the surrounding plains of some phytogeographic sectors occur. The flora of inselbergs is also characterised by indicative species of anthropized ecosystem absence. However, these species are present on the surrounding plains. Indeed, the flora of inselbergs is characterised by 11 endemic species. Inselberg’s vegetation is characterised by unique plant communities such as rock pools and Afrotrilepis pilosa mats. The exploitation and mortality rates of woody plants are significantly higher on the surrounding plains than on the inselbergs. The flora and vegetation of inselbergs show the absence of indicator species of disturbed ecosystems. They present endemic and relict species and stable woody stands. Due to the steep slope, lack of suitable soil for agriculture and sacred status of someones, the inselbergs constitute a refuge for plant species and thus contribute to the conservation of biodiversity like the protected areas.